Determinants of halal food purchase intention: applying the Theory Of Planned Behavior (TPB) in predicting halal food consumption among millennial generation in Malaysia / Musdiana Mohamad Salleh, Etty Harniza Harun and Siti Meriam Ali - Mohamad Salleh, Musdiana; Harun, Etty Harniza; Ali, Siti Meriam (2019)
This study aims to examine the determinants of millennial generations in consuming halal food in Malaysia. Ajzen's Theory of Planned Behavior is used as a framework postulates three components which are attitude, subjective norms and perceived behavioral control. The role of Islamic religiosity regarding halal purchase is also investigated as one of the predictor in the research model. Data were collected from 202 respondents through self-administrated questionnaires. The respondents were between 19 to 39 years old. Finding of this study demonstrates that the intention of millennial generation consumers in consuming halal food is predominantly influence by attitude, subjective norms, perceived behavioral control and Islamic religiosity. This study extent the insights of the Muslim consumers' behaviors particularly on millennial generations. The result of this study is useful to predict the future of the halal industry in Muslim-majority countries.